MAKNA SIMBOLIK PADA PIRANTI TRADISI NYADRAN BUMI DESA SONGOWARENG KECAMATAN BLULUK KABUPATEN LAMONGAN SEBAGAI REFERENSI PENDIDIKAN BUDAYA LOKAL - Erawanto, Udin (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of the study was to identify the symbolic meaning of the uborampe tools in ambeng, cok akan and gending-gending for the tradition of salvation nyadran earth in Songowareng Village, Bluluk District, Lamongan Regency as a reference for local cultural education. The data collection uses the method of observation, in-depth interviews and documentation. The main instrument is a researcher with camera, tape recorder and writing instruments. Selection of resource persons using purposive sampling technique. The data analysis used ethnographic analysis technique developed by James P. Spradley. The results of the study: 1) uborampe ambeng tools in the form of white rice, ingkung rooster, banana rojo sesisir, serundeng, jajan pasar, and one hundred coins, 2) uborampe cok tools in the form of takir, hide and seek, merang, ordered to be tied by lawe, red onions and garlic, candlenut, chicken eggs, and roses. 3) seven sacred gendings, namely eling-eling, rangu-rangu, gonggo mino, genderuwo momong, boar strike, bondo boyo and gending angkleng. Each device in ambeng and cok akan, as well as cute in gending is a symbol that has meaning for reference to local cultural education.